An Unusual Self-Inflicted Foreign Body in the Urinary Bladder and Urethra: A Case Report (Bangladesh Journal of Urology, 2020)
Introduction: Most foreign bodies in the lower genitourinary tract are self-inserted via the urethra as the result of exotic impulses, psychometric problems, sexual curiosity, or sexual practice while intoxicated. Diagnosis of these foreign bodies can be done by clinical history, physical examination, and image studies of the patient. The treatment of foreign bodies is determined by their size, location, shape, and mobility. In most cases, minimally invasive procedures such as endoscopic removal are recommended to prevent bladder and urethral injuries. In some cases, however, surgical treatment should be done if the foreign bodies cannot be removed by the endoscopic procedure or further injuries are expected as a result of the endoscopic procedures.Case Presentation: Herein we present a case of self-inserted lower genitourinary foreign body. A 60 years old man presented with complaints of dysuria, dribbling, haematuria and suprapubic pain for 3 weeks. An X-ray of the pelvis showed a coiled up radio opaque shadow of telephone wire in the bladder region extending downwards which was removed by suprapubic cystostomy.Discussions: Bladder foreign body is not common. Plain radiograph is sufficient to diagnose and minimally invasive procedure is usually successful. In this case retrieval by cystostomy was done to avoid the risk of bladder and urethral injury.Conclusion: Introduction into the bladder may be through self-insertion, iatrogenic means or migration from adjacent organs. Extraction should be tailored according to the nature of the foreign body and should minimize bladder and urethral trauma. The possibility of an intravesical foreign body should be considered in any patient with chronic unexplained lower urinary tract symptoms.Bangladesh Journal of Urology, Vol. 18, No. 2, July 2015 p.94-97